Relation between head and eye movement and neck and shoulder complaints in presbyopic VDU users. (April 2014) - Friedrich, Michaela; Kothe, Janette; Seidel, Egbert; Beyer, Lothar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose In subjects with neck-shoulder complaints at visual display unit (VDU) work places (>4 hours daily) the influence through a multifocal lens design on the head-eye-movement was examined. Materials and methods The head-eye-movement (head-eye-mover ratio horizontal) was determined in 100 presbyopic subjects with the Vision Print® (Essilor). The subjects were randomized and single-blind divided to three different interventions, group I: head-, II: eye-mover design, III: nearwork design, and a control group with no intervention. Results In presbyopic subjects with neck-shoulder discomfort a workstation seams to contribute to the manifestation of the pathological stereotype eye mover in the horizontal gaze shift. With the multifocal lenses a significant reduction in complaints in the shoulder and neck area for the groups I, II and III was found. The change of the head-eye-mover ratio (horizontal) in the direction of increased head movement was shown tendencially in all supplied groups, but not in the control group. Conclusion If a patient with neck-shoulder complaints needs an optometric treatment (single or multifocal glasses) a modification of the work place is required and the supply with spectacles has to take place before a therapeutic intervention. On top of this a consultation for movement stimulating working conditions must take place.